Burp tax: Regulation and revenue potential in Indonesia - Ihsan, Muhammad; Rakasiwi, Devina Aurellia (Educoretax, 2024)
The increasingly urgent phenomenon of climate change requires concrete actions from various sectors, including the livestock sector which is a significant contributor to greenhouse gas emissions, particularly methane. This study explores the potential of implementing Burp Tax in Indonesia as a regulatory mechanism to reduce methane emissions from beef and dairy cattle farms. By referring to New Zealand's experience as a Burp Tax pioneer, this study analyzes the policy scheme that includes tax subjects, tax objects, tariffs, and fair and efficient collection mechanisms. In addition, this study identifies various obstacles that may be faced in the implementation of Burp Tax in Indonesia and provides recommendations to support the national commitment in achieving the Zero Emission target in 2045/2060. The research used qualitative methods with literature study data collection techniques. The research concludes that there is great potential for the imposition of Burp Tax, so that in addition to being a form of effort to reduce methane emissions from beef and dairy cattle farms, Burp Tax can also increase the portion of state revenue from the taxation sector. The specific tariff scheme is IDR30/KgCH4 with tax subjects in the beef and dairy cattle farming sector, including individuals with 30 cows and business entities. However, it is important to note that the imposition of Burp Tax may have an economic impact on livestock business actors and affect the price of meat and milk commodities. Therefore, further studies are needed regarding the potential and impact of Burp Tax implications in Indonesia. The results of this study are expected to make a significant contribution to the development of sustainable taxation policies that are responsive to the challenges of climate change.